Family group conferences: from Maori culture to decision-making model in work with late modern families in Norway†. Issue 6 (1st November 2016) - Thørnblad, Renee; Strandbu, Astrid; Holtan, Amy; Jenssen, Toril
Abstract : Models and methods within social work and child protection services are disseminated across cultural and national borders. The family group conference (FGC), with its origins in traditional Maori culture, is one example of this. The application of this model presupposes an 'extended family'. Based on sociological theory, we highlight and problematise the explicit inattention to relevant cultural differences. The assumed existence of the extended family is implied in the direct translation of the term. The family in late modern society is often described as diversified, elective and shifting. We argue that FGC is relevant to such families. In our conclusion, we point out that despite changes, the family remains associated with traditional family values as solidarity and joint obligations, responsibilities and continuity. FGC vitalise traditional family values and facilitate for modern families performing traditional family practices. From our exploration of discourses and analyses on how FGC may be transformed from supporting Maori traditional culture to become a decision model in a CPS of a society such as Norway, we find there is a compliance with two fundamental factors: the late modern family's negotiating practices and the revitalisation of traditional family values .